2015
DOI: 10.15174/au.2015.774
|View full text |Cite
|
Sign up to set email alerts
|

Design and simulation of an optimized electrothermal microactuator with Z-shaped beams

Abstract: The displacement of the central shuttle of a Z-shape chevron actuator can be calculated using a developed approach from other authors. Who demonstrated that the actuators with this geometry offer a larger displacement compared with V-shape actuators. Z-shape offers a larger stiffness and output force for the case of only one arm.  This paper is focused on the optimization of the Z-shaped beams of a chevron actuator of eight beams, which seeks to increase the previously described response. The structure is desi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…. This indicates the measured displacement is a second-order function of voltage, as revealed by the analytical model as in (12). Large deviation occurs when the voltage exceeds certain values.…”
mentioning
confidence: 70%
See 3 more Smart Citations
“…. This indicates the measured displacement is a second-order function of voltage, as revealed by the analytical model as in (12). Large deviation occurs when the voltage exceeds certain values.…”
mentioning
confidence: 70%
“…Despite the difference in nature, the voltage and external force are equivalent in terms of generating actuator displacement and force. Rewriting (12), we have where…”
Section: System Modellingmentioning
confidence: 99%
See 2 more Smart Citations
“…The results showed that these structures may have high mechanical stiffness; which limits their actuation bidirectionally and may increase the required thermal voltages for their operations. Teopoyoti -Torres et al [22] optimized the Zactuators based on a finite element model. The results show 50 % increases in the displacement compared to Vshape actuators.…”
Section: Introductionmentioning
confidence: 99%